Melted and recrystallized holey-graphene-reinforced aluminum composites: Structure, elasticity and strength. (15th July 2022) - Guarda, Cátia; Faria, Bruno; Silvestre, Nuno; Lopes, José N.C.; Pugno, Nicola M.
Highlights: Aluminum-holey-graphene nanocomposites (NC) were simulated by MD. Al-NC were melted and recrystallized. Aluminum crystallization in the nanocomposites was about 85%. NC with undoped nanofillers showed an increase in Young's modulus between 15 and 27 % relative to pure AL, while doped nanofillers showed no improvement. The inverse rule of mixtures enabled a very good prediction of the Young's moduli of NC. Abstract: This paper aims to investigate the elasticity, strength and failure of aluminum (Al) nanocomposites with holey-graphene (hG), which were melted and recrystallized. Five nanocomposites (Al-graphene and four Al-hG - two of them doped, with nitrogen and boron) were studied by molecular dynamics simulations. They were melted and subsequently recrystallized at a fixed cooling rate of 0.25 K/ps. The nucleation temperature of nanocomposites was increased by 300–200 K compared to pure aluminum. The Al crystallization in the nanocomposites was about 85 % (97 % for pure Al). The nanocomposites with undoped nanofillers showed an increase in Young's modulus between 15 and 27 % relative to pure Al, while doped nanofillers showed no improvement. The mechanical properties of the nanocomposites depended on the characteristics of the nanofillers, namely (i) the porosity, (ii) the percentage of recrystallization of the Al matrix, and (iii) the interfacial adhesion in the interface Al-nanofillers. The results show that undoped nanofillers have much higher Young's modulus and lower porosity compared to the doped nanofillers (N-hG and B-hG). Finally, the application of the inverse rule of mixtures to extract the Young's modulus of the nanocomposite was successful.